2004
DOI: 10.1523/jneurosci.0836-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of External Pallidal Segment in Primate Parkinsonism: Comparison of the Effects of 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine-Induced Parkinsonism and Lesions of the External Pallidal Segment

Abstract: These experiments re-examined the notion that reduced activity in the external pallidal segment (GPe) results in the abnormalities of neuronal discharge in the subthalamic nucleus (STN) and the internal pallidal segment (GPi) and in the development of parkinsonian motor signs. Extracellular recording in two rhesus monkeys, which had been rendered parkinsonian by treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), revealed that the average neuronal discharge rate decreased in GPe but increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
185
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(209 citation statements)
references
References 54 publications
(56 reference statements)
18
185
1
1
Order By: Relevance
“…However, how DA depletion could affect this contribution depends crucially on the degree of segregation between the direct and indirect pathways. Because recent experiments indicate that this is incomplete (Aizman et al, 2000;Wu et al, 2000;Levesque and Parent, 2005), we suggest that the indirect pathway only plays a secondary role in the emergence of pathological oscillations in GPi and impairment of movement, in line with Soares et al (2004).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, how DA depletion could affect this contribution depends crucially on the degree of segregation between the direct and indirect pathways. Because recent experiments indicate that this is incomplete (Aizman et al, 2000;Wu et al, 2000;Levesque and Parent, 2005), we suggest that the indirect pathway only plays a secondary role in the emergence of pathological oscillations in GPi and impairment of movement, in line with Soares et al (2004).…”
Section: Discussionsupporting
confidence: 62%
“…This value or greater was considered to indicate a significant probability ( p Ͻ 0.05) of synchronized oscillatory activity between two cells. For statistical analysis of the autospectra, the elements of the interspike intervals of each spike train were randomly shuffled, and the power spectrum of the resulting (random) spike train was calculated (Soares et al, 2004). The mean and SD of the resulting power spectra of 20 iterations of shuffled data were computed.…”
Section: Numerical Simulations Of the Detailed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that, in the parkinsonian state, DBS acts not as an informational lesion, but as an "information filter" (Rosenbaum et al, 2014) or a desynchronizing force (Wilson et al, 2011). We speculate that DBS may permit the transmission of task-related information through the BG while blocking the transmission of some of the resting pathologic firing characteristics of PD, such as low-frequency oscillations in the STN Levy et al, 2002;Soares et al, 2004;Meissner et al, 2005;Kühn et al, 2008;Moran et al, 2008;McConnell et al, 2012) and GP (Wichmann et al, 1994(Wichmann et al, , 1999Raz et al, 2000;Brown et al, 2004;McCairn and Turner, 2009). A filter or desynchronizing effect of DBS (Wilson et al, 2011;Rosenbaum et al, 2014) could explain the divergent motor (Slavin et al, 2004;Alvarez et al, 2005;Merello et al, 2006;Baraduc et al, 2013) and cognitive (Brown et al, 2003;Carbon and Eidelberg, 2006;) effects that follow lesions of the BG versus stimulation of the same structures.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, as new experimental data are acquired, adjustments must be made to the conceptual and computational basal ganglia models. For example, Soares et al (2004) showed that MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-induced parkinsonism in rhesus monkeys reduced GPe activity (and thus increased STN and GPi activity) as predicted. However, ablation of the GPe did not induce parkinsonian symptoms.…”
mentioning
confidence: 92%